TEATER SEKOLAH AJANG KREATIVITAS DAN MASA DEPAN SENI TEATER [Schools’Theater as a Media to Improve Creativity and the Future of Theater itself] - I Gusti Ayu Agung Mas Triadnyani; Maria Matildis Banda; I Ketut Nama (TOTOBUANG, 2021)
Theater as one of the extra-curricular activities in Senior High-school gradually attract more students to join. The previous reseaches provedg their  interesting on it. Based on  several undergone activities, there was 40% students who stated that their joining in the literary community  in schools due to the existence of the theater. This research aims to more deeply explore the characteristics of theater in schools, especially the Senior High-Schools which located in the three districts of Bali. The method applied is due to field-method combined by library research. The techniques are  questionnaires and interviews. As a result, the students have great interests in play theater because they think that  this kind of activity is the arena to self improve and also to stimulate creativity. Kegiatan teater sebagai salah satu kegiatan ekstrakurikuler yang ada di SMA semakin lama semakin diminati. Penelitian terdahulu membuktikan bahwa minat siswa pada kegiatan ini sangat tinggi. Dari beberapa kegiatan yang diselenggarakan, 40% siswa menyatakan bahwa mereka bergabung dengan komunitas sastra di sekolah karena adanya kegiatan teater. Penelitian ini bertujuan untuk menggali lebih dalam karakteristik teater sekolah, khususnya di tingkat SMA yang ada di tiga kabupaten di Bali. Metode yang digunakan adalah metode lapangan yang didukung studi pustaka. Teknik yang dipakai adalah kuesioner dan wawancara. Hasil yang diperoleh adalah bahwa siswa-siswi menyukai kegiatan teater/drama karena kegiatan ini dapat menjadi ajang pengembangan diri siswa, di samping membangkitkan kreativitas.